Makna Simbolisme Pokok Anggur Yoh. 15:1-8 Dalam Korelasinya Dengan Koinonia Gereja - Irenius Pita Raja Boko; Arnoldus M. Paga; Alexander Ngozo; Marianus C. D. Taluk; Yosefino R. Reda; Moris N. Bai (CV. Multi Kreasi Media, 2023)
The aim of this research is to find out the meaning between the Vine’s symbolisms in John 15:1-8 in relation with the Church Koinonia. This research uses the qualitative method, most especially the literature review. By exercising this literature review, the author discover that the meaning of the Vine symbolism in John 15:1-8 is the identity of Jesus himself. The Evangelist describes that Jesus is the true vine and the Church Koinonia are the brances which should depend absolutely on Him (the true Vine) in order to change.